2018
DOI: 10.3390/molecules23102626
|View full text |Cite
|
Sign up to set email alerts
|

Biodetoxification of Phenolic Inhibitors from Lignocellulose Pretreatment using Kurthia huakuii LAM0618T and Subsequent Lactic Acid Fermentation

Abstract: Phenolic inhibitors generated during alkaline pretreatment of lignocellulosic biomasses significantly hinder bacterial growth and subsequent biofuel and biochemical production. Water rinsing is an efficient method for removing these compounds. Nevertheless, this method often generates a great amount of wastewater, and leads to the loss of solid fiber particles and fermentable sugars. Kurthia huakuii LAM0618T, a recently identified microorganism, was herein shown to be able to efficiently transform phenolic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Zhu et al [2010] showed that lignin degradation during the alkaline pretreatment of corn stover was in the range 9.1% to 46.2% (w/w) depending on NaOH loading that was changed from 1.0% to 7.5% w/w for solidstate. Many studies confirm that phenols may hinder the bacterial growth in the subsequent biological processes of biofuel production from the pretreated biomass [Kim, 2018;Xie et al, 2018]. The phenols concentration in the feedstock examined in this experiment was not very high (Table 2.)…”
Section: The Biogas Production and Compositionsupporting
confidence: 50%
“…Zhu et al [2010] showed that lignin degradation during the alkaline pretreatment of corn stover was in the range 9.1% to 46.2% (w/w) depending on NaOH loading that was changed from 1.0% to 7.5% w/w for solidstate. Many studies confirm that phenols may hinder the bacterial growth in the subsequent biological processes of biofuel production from the pretreated biomass [Kim, 2018;Xie et al, 2018]. The phenols concentration in the feedstock examined in this experiment was not very high (Table 2.)…”
Section: The Biogas Production and Compositionsupporting
confidence: 50%
“…Glucose, xylose, LA, acetic acid, and formic acid were analyzed using an Agilent 1200 HPLC system (Agilent Technologies Co. Ltd, Palo Alto, CA, USA), equipped with an RID‐10A detector or an SPD‐20A detector, and a Bio‐Rad Aminex HPX‐87H (Hercules, CA, USA), column at the column temperature of 40 °C, as we reported previously . The concentrations of vanillin, syringaldehyde, and p ‐hydroxybenzaldehyde were measured using the HPLC method as we reported previously . The total content of phenolic compounds in the samples was determined by the Folin–Ciocalteu method, with gallic acid as the calibration standard.…”
Section: Methodsmentioning
confidence: 99%
“…These bacteria may play a role in nitrification, as hypothesized by Kellogg et al (2016) in corals. One strain of the genus Kurthia has been shown to transform phenolic compounds into acids that are less toxic (Xie et al, 2018).…”
Section: Discussionmentioning
confidence: 99%